Two-Weight Criteria for the Multidimensional Hardy-Type Operator in p-Convex Banach Function Spaces and Some Applications - Bandaliev, R.A. (Український математичний журнал, 2015)
The main aim of the paper is to prove a two-weight criterion for the multidimensional Hardy-type operator from weighted Lebesgue spaces into p-convex weighted Banach function spaces. The problem for the dual operator is also considered. As an application, we prove a two-weight criterion of boundedness of the multidimensional geometric mean operator from weighted Lebesgue spaces into weighted Musielak–Orlicz spaces. Головною метою даної статті є доведення двовагового критерію для багатовимiрного оператора типу Хардi із вагових лебегових просторів в p-опуклі вагові банахові простори функцій. Також розглянуто задачу для дуального оператора. Як застосування, встановлено двоваговий критерій обмеженості багатовимірного оператора геометричного середнього з вагових лебегових просторів у вагові простори Мусєляка-Орліча.